Respuesta :

PLEASE MAKE THIS BRAINLIEST COMMENT IF THIS HELPED! I NEED ONE MORE BRAINLIEST ANSWER!!

{y,x} = {-7,-3} is ya solution!

 {Steps that may help with future questions}

      [1]    y - 3x = 2

     [2]    y - 2x = -1

Graphic Representation of the Equations :

   -3x + y = 2        -2x + y = -1  

// Solve equation [2] for the variable  y

 [2]    y = 2x - 1

// Plug this in for variable  y  in equation [1]

  [1]    (2x-1) - 3x = 2

  [1]     - x = 3

// Solve equation [1] for the variable  x

  [1]    x = - 3

// By now we know this much :

   y = 2x-1

   x = -3

// Use the  x  value to solve for  y

   y = 2(-3)-1 = -7